PH (Phiezoelectric on Hydraulic Ram Pump) Media Supplier of Water and Producing Electrical Energy Environment Friendly - Dienullah, R. M. A.; F. K. Aini; F. Febriana; F. Rosariawari (Future Science)
In this time, water and electricity are some of the most important components of human life in this 20th century, both in daily activities and in work. Water and electricity are also resources that should be massively exploited for the benefit to be felt by all elements of society. However, problems occur when geographical factors and infrastructure factors become an obstacle in supporting the availability of these resources. Geographical factors in the form of areas far from water sources, as well as the location of areas far from the reach of the government so that there is a gap in the development in the distribution of infrastructure within a region. This causes some elements of society, especially in backward villages, cannot benefit fully from these resources. To overcome the crisis, then we try to innovate by making a development and upgrade of a hydram pump by adding piezoelectric material as a source of electricity to make hydram more efficient than the latest version and have more value on the renewable energy side. Then, we will put the piezoelectric material into the series of hydram pump so that the rural community will be left behind will be able to feel the water and electricity resources of our innovations are simultaneously environmentally friendly.